2014
DOI: 10.1371/journal.pone.0109701
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Mitochondrial Genome of Aix galericulata and Tadorna ferruginea: Bearings on Their Phylogenetic Position in the Anseriformes

Abstract: Aix galericulata and Tadorna ferruginea are two Anatidae species representing different taxonomic groups of Anseriformes. We used a PCR-based method to determine the complete mtDNAs of both species, and estimated phylogenetic trees based on the complete mtDNA alignment of these and 14 other Anseriforme species, to clarify Anseriform phylogenetics. Phylogenetic trees were also estimated using a multiple sequence alignment of three mitochondrial genes (Cyt b, ND2, and COI) from 68 typical species in GenBank, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 27 publications
6
34
1
Order By: Relevance
“…All the mitogenome genes were encoded on the H strand except for one proteincoding gene (ND6) and eight tRNA genes, similar to typical Anseriformes mtDNAs (Liu et al 2013). The composition of base composition in Shengjin Lake Tadorna tadorna indicating a remarkably high AT content and a low GC content, which is similar observed in other Anatidae mt genomes (Liu et al 2013(Liu et al , 2014. All the start codon of the protein-coding genes is ATG, and TAA is the most frequent stop codon.…”
supporting
confidence: 55%
“…All the mitogenome genes were encoded on the H strand except for one proteincoding gene (ND6) and eight tRNA genes, similar to typical Anseriformes mtDNAs (Liu et al 2013). The composition of base composition in Shengjin Lake Tadorna tadorna indicating a remarkably high AT content and a low GC content, which is similar observed in other Anatidae mt genomes (Liu et al 2013(Liu et al , 2014. All the start codon of the protein-coding genes is ATG, and TAA is the most frequent stop codon.…”
supporting
confidence: 55%
“…; Robertson & Goldstein ; Liu et al . ; Sun et al . ) point to many independent derivations of diving adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the most comprehensive molecular phylogeny to date using 16 complete mitochondrial sequences and three mitochondrial genes (Cytochrome b , ND2, COI) from 68 species of anatids, Liu et al . () identified Dendrocygna, Erismaturinae and Anserinae as successive sister groups of Anatinae (Liu et al . ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Membership to the same clade has been demonstrated on the basis of multiple sequence analyses, including: an analysis of a region of mtDNA spanning a region of cytochrome b (Sraml et al 1996), of the D-loop region (Donne-Goussé et al 2002), the COI gene also present in the mitochondrial genetic material (Jin et al 2012), the ND2 gene (Mitochondrially Encoded NADH: Ubiquinone Oxidoreductase Core Subunit 2) (Liu et al 2014), and the complete sequence of the mitochondrial DNA (Liu et al 2014, Zhang et al 2017. These studies have also indicated that the Mandarin Duck and the Mallard (Anas platyrhynchos) fall into separate phylogenetic clades and are separated by several phylogenetic nodes, the exact number of which depends on the sequences analyzed and the method of phylogenetic tree construction (Sraml et al 1996, Donne-Goussé et al 2002, Jin et al 2012, Liu et al 2014, Zhang et al 2017. The different phylogenetic position of the two species may contribute to them being unable to hybridize (Donne--Goussé et al 2002).…”
Section: Review Of Speciesmentioning
confidence: 99%